AESTHETIC AND ARTISTIC APPRECIATION OF B-40 - Batlawala, Dipti Ashok kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Janamsakhi manuscript deals with the first Guru of Sikhs, Nanak Dev. Janamsakhi is birth stories of Guru Nanak. The sakhis (stories) in Janamsakhi manuscripts were like an artistic instrument to spread and share the teachings of the Gurus more effectively with the help of visuals as these facilitated the understanding of thought and helped the people to relate to the age and the legend. The popularity of Janamsakhis in the society increased due to their usefulness. Most of the people were illiterate at that time, so these paintings in Janamsakhi were a cagiest way to teach the doctrines of Sikhism to the people. These paintings upheld the Sikh aesthetics to reinforce spirit of the Janamsakhi tradition.